PENGEMBANGAN SISTEM INFORMASI PELAPORAN KINERJA GURU - Masyfa, Laila Maghfirotul; Khafidhoh, Nur (Lembaga Penelitian Pengabdian Masyarakat Universitas KH. A. Wahab Hasbullah, 2021)
The performance appraisal information system is a formal system designed to periodically evaluate a person's performance to produce information and effectiveness to achieve certain goals in the world of education, especially at Madrasah Ibtidaiyah Sayyid Abdurrohman II Pagerwojo Perak Jombang. and simplify the process of assessing teacher performance starting from data collection to producing teacher performance appraisal reports so that the authors make applications to facilitate teacher performance assessments by processing data quickly. This information system is expected to meet the criteria of a valid and practical teacher performance appraisal system. The method used in system development using the Rnd method with development tools and materials using the PHP and MysQl programming languages. Data collection techniques used are observation, interviews, and documentation. This study resulted in a teacher performance appraisal information system that can provide convenience in web-based personnel performance appraisal activities to make it easier to determine the level of validity, practicality and reliability.